2018
DOI: 10.1007/s00018-018-2754-7
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional motility of kinesin-5 motor proteins: structural determinants, cumulative functions and physiological roles

Abstract: Mitotic kinesin-5 bipolar motor proteins perform essential functions in mitotic spindle dynamics by crosslinking and sliding antiparallel microtubules (MTs) apart within the mitotic spindle. Two recent studies have indicated that single molecules of Cin8, the Saccharomyces cerevisiae kinesin-5 homolog, are minus end-directed when moving on single MTs, yet switch directionality under certain experimental conditions (Gerson-Gurwitz et al., EMBO J 30:4942-4954, 2011; Roostalu et al., Science 332:94-99, 2011). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 154 publications
2
57
0
Order By: Relevance
“…Recently, it has become clear that fungal Kinesin-5s including Cut7 are bidirectional motors; they display either plus end-directed or minus end-directed motilities depending upon conditions (eg. the degree of motor crowding on the microtubule lattice) [59][60][61] . Under our experimental conditions, we did not detect a similar bi-directionality, despite Klp9 forming homotetramers like Cut7.…”
Section: Kinesin-6 Klp9 Is a Processive Plus End-directed Motormentioning
confidence: 99%
“…Recently, it has become clear that fungal Kinesin-5s including Cut7 are bidirectional motors; they display either plus end-directed or minus end-directed motilities depending upon conditions (eg. the degree of motor crowding on the microtubule lattice) [59][60][61] . Under our experimental conditions, we did not detect a similar bi-directionality, despite Klp9 forming homotetramers like Cut7.…”
Section: Kinesin-6 Klp9 Is a Processive Plus End-directed Motormentioning
confidence: 99%
“…Proteomic studies identified 3 kinesins expressed during male gametogenesis (kinesin-8B, -13 and -15)(Khan et al, 2005;Talman et al, 2014), but no functional studies have been conducted until now. In other eukaryotes, orthologues for kinesin-4, -5, -8B, -13 and -15 are known to be involved in microtubule dynamics and particularly mitosis and cilia/flagella length regulation(Almeida & Maiato, 2018;Hu et al, 2015;Ma, Wang, & Yang, 2017;Muhia et al, 2016;Niwa, 2015;Niwa et al, 2012;Shrestha, Hazelbaker, Yount, & Walczak, 2018;Singh, Pandey, Al-Bassam, & Gheber, 2018;van Riel et al, 2017). Unfortunately, concerning PBANKA_0622400, PBANKA_0609500, PBANKA_0809500, PBANKA_0902400 and PBANKA_1224100, no functional data are available and the number of species possessing orthologues of these proteins is currently very limited, making it difficult to construct any hypothesis concerning their roles.…”
mentioning
confidence: 99%
“…These results led us to check the behaviour of Cin8 upon DNA damage in telophase. Cin8 is a bidirectional mitotic kinesin-5 motor that slide away antiparallel interpolar microtubules, thus favouring spindle elongation in anaphase (Khmelinskii et al 2009;Singh et al 2018). Upon phleomycin treatment, Cin8 relocated from the spindle to two discrete foci in telophase-blocked cells (Fig 3d).…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, a partial dephosphorylation of Cin8 occurs upon DNA damage in telophase. We hypothesize that this Cin8 relocalization is likely a consequence of its novel minus-end-directed motility (Singh et al 2018), and might reset the spindle to revert its elongation in cells already in late-anaphase.…”
Section: Resultsmentioning
confidence: 97%